Theatricalities – A Term’s Breadth (KULT_online, 2016)
This volume of Germanoslavica discusses various aspects of theatricality without insisting on a constricted definition of the term. Having different academic backgrounds, the authors present a wide spectrum of research fields, highlighting the many facets of theatricality. What is excellently demonstrated is how the term is contextualized – historically, genre specifically, etc. – in each separate case. Through the selected approach, the term becomes a complex tool for analysis.